ANALISIS ARTIKEL ILMIAH BIDANG ILMU MARITIM DALAM MENDUKUNG REPOSITORI NASIONAL - Royani, Yupi; Margono, Tri; Sulaiman, Madiareni (BACA: Jurnal Dokumentasi dan Informasi, 2019)
The aim of this research are to find out: (1) data proceed from database with the topic maritime and marine that can access by the user through the OPAC: (2) precision of the data in database: (3) the precision between data proceed by the standard tabulation of literature (keyword) and title in database; (4) the precision between data was inputed with content and metadata field. Result of the extract data from ISJD is descriptor (keyword) Maritime Field (25 pieces keyword from 609 article title) tabulated and made the matrix by excel office. Data that have been collected will be validated base on the recall result, and the precision it will be analyzed descriptively. It found that in Maritime field the descriptor used as keyword was 25 pieces. The keywords were: marine alga as food, ocean mining, marine park and reserves, marine chemical ecology, marine biodiversity, marine law, maritime policy, maritime industry, marine mineral resources, maritime safety, marine biological diversity, loading and unloading, marine ecosystem, marine resources, marine pharmacology, marine resources conservation, marine ecology, marine tourism, marine fisheries, marine environmental, ports, marine shipping, marine pollution, maritime law, and marine transportation. The number of article is found based on keywords.